ANALISIS KESULITAN SISWA DALAM MEMECAHKAN SOAL-SOAL FISIKA KELAS XI SMA NEGERI 9 - Aufah, Rahmatul; Sudrajat, Hendar; Azizahwati, Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to analyze the student’s difficulties in solving the problems based on the stages of solving problems skills at XI science 4 class of Senior High School 9 at Pekanbaru. This research was caused by the study results of TIMSS (Trends in International Mathematics and Science Study) that showing Indonesia's students are at a very low ranking in the ability of the theory, analysis and problem solving. The respondents in this research were 35 students of XI science 4 class of Senior High School 9 at Pekanbaru. The techniques used to collect data consisted of diagnostic test. The instrument in this research are the diagnostic tests and sheets appraisement students based on stages of problem solving skills. Stages of problem solving skills are (1) understanding the problem, (2) devising the plan, (3) Carryng out the plan and (4) looking back. Data analysis techniques used descriptive analysis by calculate the percentage of students who are having difficulties in solving problems of physics based on ideal boundary pass and sheets appraisement students. Based on the diagnostic test got understanding the problem (32,6 %) included in a category almost half have difficulty, devising the plan (30,03%) included in a category almost half have difficulty, carryng out the plan (26,87%) included in a category almost half have difficulty and looking back (84,28%) included in a category in general have difficulty.Key Words: Problem Solving Skills, Diagnostic Test, Physic Learning